The effect of zeolite on inkjet coated paper surface properties and deinking - ÖZCAN, ARİF; TUTAK, DOĞAN (WALTER DE GRUYTER GMBH, 2020)
Coatings are generally applied for opacity, smoothness and gloss on the paper surface. Pigments such as CaCO3, Kaolin-Clay and Zeolite are used, and natural or synthetic binders are used. In this study, coatings using the CaCO3, Kaolin-Clay and Zeolite pigments on 80 gr/m(2) high grade papers were made. PVOH was used as binder. Following coating, papers were processed through supercalendering and printed with inkjet printer. Using INGEDE method 11p. recycling process printed papers were deinked. The optical properties of the recycled papers obtained after the deinking treatment, were compared with the unprinted papers. At the end of the study, the effect of coating on paper surface and the recycling performances of the inkjet printed papers were revealed. It was determined that the papers in which zeolite was used as a pigment were better, in terms of both surface properties and recycling performance when surface properties and recycling performance of coated papers were examined. When all the results were compared, it was found that the performances of coatings for which zeolite was used were much better than coatings such as CaCO3 and Kaolin-Clay, both in terms of surface coating properties such as opacity, roughness and gloss and recycling results such as brightness.
Keywords: coating; inkjet printing; paper; recycling; zeolite; ENZYMATIC DEINKING; PIGMENTS; PULP